2014
DOI: 10.5539/jas.v6n2p33
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Composition and Population Dynamics of Arthropods in the Genetically Modified Soybeans Roundup Ready® RR1 (GT 40-3-2) and Intacta RR2 PRO® (MON87701 x MON89788)

Abstract: Knowledge of insect diversity is essential for ecological studies and pest management. The aim of this study was to study the occurrence, abundance of target and non-target pests in genetically modified insect resistant (Bt) and glyphosate-tolerant soybeans (RR1 and RR2), with and without the application of insecticides. Experiments were carried out in the agricultural year of 2011/2012 in four municipalities in the State of Mato Grosso do Sul. The treatments were: 1 -Roundup Ready ® RR1 soybeans without insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 19 publications
0
8
0
12
Order By: Relevance
“…A study of diversity, composition, and population dynamics of arthropods in non-Bt soybean and Bt soybean showed that A. gemmatalis , C. includens , C. virescens , and S. frugiperda were significantly controlled by Bt soybean. However, other species of the Spodoptera complex were not controlled by this technology [ 70 ]. Other studies reported that S. cosmiodes was the most abundant species attacking Bt soybean [ 71 ] and that development and reproduction of this species were not affected by the Cry1Ac protein [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study of diversity, composition, and population dynamics of arthropods in non-Bt soybean and Bt soybean showed that A. gemmatalis , C. includens , C. virescens , and S. frugiperda were significantly controlled by Bt soybean. However, other species of the Spodoptera complex were not controlled by this technology [ 70 ]. Other studies reported that S. cosmiodes was the most abundant species attacking Bt soybean [ 71 ] and that development and reproduction of this species were not affected by the Cry1Ac protein [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ministério da Agricultura and Abastecimento 2013). Although new technologies such as Bt-transgenic soybean expressing the Cry1Ac toxin have been commercially released in Brazil (Justiniano et al 2014), there is little expectation that they will be effective in controlling SAW due to the low toxicity of Cry1Ac to S. eridania larvae (Santos et al 2009, Bernardi et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The main soybean Lepidopteran pests are velvetbean caterpillar, Anticarsia gemmatalis (Hübner), soybean looper, Chrysodeixis includens (Walker), Old World bollworm, Helicoverpa armigera (Hübner), and tobacco budworm, Chloridea virescens (F.). [3][4][5][6] However, outbreaks of Spodoptera species have been reported in soybean fields, including S. frugiperda (Smith), S. eridania (Stoll), S. cosmioides (Walker) and S. albula (Walker). [7][8][9] Of these species, S. frugiperda is an emerging soybean pest due to increased infestations and damage observed on soybean in recent seasons in Brazil.…”
Section: Introductionmentioning
confidence: 99%